Analisis Usaha Ternak Itik Petelur Sebagai Sumber Pendapatan Peternak Lokal - Putri, Tria Syah (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the feasibility and contribution of duck egg farming as a source of income for local farmers. Using a descriptive quantitative approach, data were collected through interviews, questionnaires, observations, and documentation involving 40 duck egg farmers. The results indicate that duck egg farming provides significant income for farmers, with an average productivity rate of 60–70% of the total population and a monthly net profit ranging from IDR 3,000,000 to IDR 4,500,000 per farmer. The cost analysis shows that feed accounts for 65–70% of total production costs, making it the most dominant expenditure. Despite this, the use of alternative local feed sources has proven effective in reducing costs without decreasing productivity. The financial analysis reveals that the average Revenue Cost Ratio (R/C ratio) is 1.45, indicating that duck egg farming is economically feasible and profitable. Beyond financial benefits, this business also provides social contributions, including family employment opportunities and community empowerment in rural areas. However, challenges remain, such as limited capital access, fluctuating feed prices, and weak bargaining power in marketing. Therefore, policy support, farmer group empowerment, and access to financing are crucial to enhance sustainability. Overall, duck egg farming plays a strategic role in improving local farmers’ livelihoods and has strong potential to be developed further as a sustainable rural agribusiness.